Improving the accuracy of hybrid scanning 3D fiber-optic measuring heads with an acousto-optic feedback sensor for contact and non-contact coordinate measurements of product sizes - E. V. Leun; A. E. Shakhanov (Омский научный вестник)
The article presents a method for determining the elastic deformations arising from the mechanical contact of a spherical tip and a product, which makes it possible to exclude the influence of material deformations like «pile-up». Paper discusses the construction of a hybrid 3D scanning fiber-optic measuring head (FOMH) with the formation of scanning laser beam motion within the angular sector of the 180°×180° hemisphere based on a low-coherence interferometer, a spatial light modulator based on a fiber-optic piezoscanner and a «fisheye» lens. The possibilities of high-precision two-coordinate measurements of the scanning laser beam due to the use of an acousto-optic modulator in the FOMH feedback sensor as a space-sensitive transducer are considered.